Pengaruh Kualitas Pelayanan Publik terhadap Tingkat Kepuasan Masyarakat Pengguna Pelayanan Administrasi Terpadu (Paten) Kecamatan Ngamprah - Mega Oktaviawati; Agustina Setiawan; Wawan Gunawan (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
The research conducted aims to analyze the impact of public service quality on the level of public satisfaction in Ngamprah District, particularly in the implementation of the District Integrated Administration Service System (PATEN). Using simple linear regression analysis, this study evaluates the relationship between public service quality (X) and public satisfaction (Y). Data was collected from 33 respondents through questionnaires measured using a Likert scale. The analysis results indicate that public service quality has a significant impact on public satisfaction, with a regression parameter value of 0.423 and a significance value of 0.000. The coefficient of determination, or R Square, is valued at 0.771, indicating that 77.1% of the variance in public satisfaction can be explained by the quality of public service. This study concludes that improvements in public service quality are directly associated with increases in public satisfaction. The findings highlight the importance of focusing on service aspects such as timeliness, ease of access, service model variety, accuracy, completeness, courtesy, responsibility, friendliness, and comfort to achieve higher service standards and enhance public trust.